A fully automated and validated human plasma LC–MS/MS assay for endogenous OATP biomarkers coproporphyrin-I and coproporphyrin-III. (11th May 2018) - King-Ahmad, Amanda; Clemens, Sara; Ramanathan, Ragu; Zhang, Yanhua; Raha, Nancy; Zhang, Yizhong; Holliman, Christopher; Rodrigues, A David; Li, Fumin
Aim: A validated LC–MS/MS assay for the quantitation of coproporphyrin-I and -III (CP-I, CP-III) in human plasma has been developed to understand the utility of both as possible endogenous biomarkers for organic anion-transporting polypeptides (OATP)-mediated drug–drug interactions (DDIs).Materials and Methods: Human plasma extracts were analyzed for CP-I and CP-III using a Sciex API 6500+ mass spectrometer. Results: The assay was utilized for plasma samples from a clinical DDI study involving a new chemical entity that presented as an OATP inhibitor in vitro . A formal DDI study, with a probe drug (atorvastatin), was also included as part of the clinical study.Conclusion: Changes in CP-I area under the plasma concentration versus time curve (AUC0–48 h ) were observed, which were similar to the AUC ratio obtained with atorvastatin. These results support the idea that plasma CP-I may have utility in Phase I by supporting the rapid assessment of OATP inhibition risk.